Factors Associated with Pasung (Seclusion and Restraint) in Indonesia: A Systematic Review - Shofi Khaqul Ilmy; Noorhamdani; Heni Dwi Windarwati (GoAcademica Research & Publishing, 2020)
Schizophrenia is a chronic and multifactorial mental health problem that occurs in developing countries, including in Indonesia. Families with schizophrenia patients will feel the burden of care and lead to pasung, and supported by various factors. Pasung, by the family, aims to control the aggressive behavior of the patient. A systematic review was conducted by searching four online databases, namely ProQuest, Science Direct, and EBSCO, and Google Scholar in the past ten years. This analysis uses the PRISMA 2009 method and obtained 14 articles for final review. The results obtained are the internal factors that most influence on pasung is the aggressive behavior of schizophrenia patients, both towards themselves, family, or the environment. In comparison, the most influential external factor is the emergence of stigma against patients and their families. Both of these factors cause the family to decide to pasung on schizophrenia patients, associated with feelings of helplessness and hopelessness. Community mental health nursing (CMHN) plays a role in handling and preventing pasung, which must be supported by the government and the community. Increased knowledge about schizophrenia and pasung in community has an impact on improving the mental health status of the community. Optimal mental health is the right of everyone throughout the world, including in Indonesia.